Control of Behavioral Arousal and Defense by a Glutamatergic Midbrain-Amygdala Pathway in Mice - Chen, Shang-Yi; Yao, Jing; Hu, Yu-Duan; Chen, Hui-Yun; Liu, Pei-Chang; Wang, Wen-Feng; Zeng, Yu-Hang; Zhuang, Cong-Wen; Zeng, Shun-Xing; Li, Yue-Ping; Yang, Liu-Yun; Huang, Zi-Xuan; et al. (Frontiers in Neuroscience, 2022)
In response to external threatening signals, animals evolve a series of defensive behaviors that depend on heightened arousal. It is believed that arousal and defensive behaviors are coordinately regulated by specific neurocircuits in the central nervous system. The ventral tegmental area (VTA) is a key structure located in the ventral midbrain of mice. The activity of VTA glutamatergic neurons has recently been shown to be closely related to sleep–wake behavior. However, the specific role of VTA glutamatergic neurons in sleep–wake regulation, associated physiological functions, and underlying neural circuits remain unclear. In the current study, using an optogenetic approach and synchronous polysomnographic recording, we demonstrated that selective activation of VTA glutamatergic neurons induced immediate transition from sleep to wakefulness and obviously increased the amount of wakefulness in mice. Furthermore, optogenetic activation of VTA glutamatergic neurons induced multiple defensive behaviors, including burrowing, fleeing, avoidance and hiding. Finally, viral-mediated anterograde activation revealed that projections from the VTA to the central nucleus of the amygdala (CeA) mediated the wake- and defense-promoting effects of VTA glutamatergic neurons. Collectively, our results illustrate that the glutamatergic VTA is a key neural substrate regulating wakefulness and defensive behaviors that controls these behaviors through its projection into the CeA. We further discuss the possibility that the glutamatergic VTA-CeA pathway may be involved in psychiatric diseases featuring with excessive defense.